2022
DOI: 10.3389/fmars.2022.809355
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere-Ocean Coupled Variability in the Arabian/Persian Gulf

Abstract: The Arabian Gulf comprises one of the world's most unique and fragile marine ecosystems; it is susceptible to the adverse effects of climate change due to its shallow depth and its location within an arid region that witnesses frequent severe atmospheric events. To reproduce these effects in numerical models, it is important to obtain a better understanding of the region's sea surface temperature (SST) variability patterns, as SST is a major driver of circulation in shallow environments. To this end, here, emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…The temporal SST trends between 1982 to 2020 were about 0.44 ± 0.06 • C/decade and 0.32 ± 0.04 • C/decade for AG and OG, respectively (Figure 3a,b). This result is in good agreement with [33], who found that the average SST trend was about 0.41 ± 0.14 • C/decade in the AG during the same period .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The temporal SST trends between 1982 to 2020 were about 0.44 ± 0.06 • C/decade and 0.32 ± 0.04 • C/decade for AG and OG, respectively (Figure 3a,b). This result is in good agreement with [33], who found that the average SST trend was about 0.41 ± 0.14 • C/decade in the AG during the same period .…”
Section: Discussionsupporting
confidence: 92%
“…The lowest MHW frequencies in both gulfs are observed from 1982 to 1992 and from 2012 to 2014 with less than one event/year. These years are considered cold years (see Figure 4a,b), with the lowest SSTA variability as already noted by [33]. We also found an interesting MHW frequency peak (~7 events/year) at AG in 2010.…”
Section: The Inter-annual Variability Of the Mhw Characteristics (198...supporting
confidence: 77%
See 2 more Smart Citations
“…The seawater in the eastern region of Saudi Arabia exposed to high rate of changes due to the expansion of industrial growth and increase in human infrastructure with other activities. In addition to global increase in atmospheric temperature, the Arabian gulf considered a shallow water body, average depth of 36 meter, which makes the consequence of changes in temperature patterns noticeable and more significant [4] [5].…”
Section: Introductionmentioning
confidence: 99%